2021
DOI: 10.1021/acsami.1c08329
|View full text |Cite
|
Sign up to set email alerts
|

Co-delivery of Phagocytosis Checkpoint Silencer and Stimulator of Interferon Genes Agonist for Synergetic Cancer Immunotherapy

Abstract: Efficient capture and presentation of tumor antigens by antigen-presenting cells (APCs), especially dendritic cells (DCs), are crucial for activating the anti-tumor immunity. However, APCs are immunosuppressed in the tumor microenvironment, which hinders the tumor elimination. To reprogram APCs for inducing strong anti-tumor immunity, we report here a co-delivery immunotherapeutic strategy targeting the phagocytosis checkpoint (signal regulatory protein α, SIRPα) and stimulator of interferon genes (STING) of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 50 publications
1
14
0
2
Order By: Relevance
“…It will be important to consider this emerging information in the design of next-generation STING agonists and delivery technologies. Several groups have already developed systems that allow for codelivery of STING agonists and therapeutics that can target other therapeutic pathways ,,,,, …”
Section: Summary Perspectives and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…It will be important to consider this emerging information in the design of next-generation STING agonists and delivery technologies. Several groups have already developed systems that allow for codelivery of STING agonists and therapeutics that can target other therapeutic pathways ,,,,, …”
Section: Summary Perspectives and Future Directionsmentioning
confidence: 99%
“…To avoid use of chemotherapy while still aiming to enhance tumor antigen uptake by APCs, Lu et al also leveraged a polymeric carrier for dual-delivery of cGAMP and an siRNA to inhibit expression of the phagocytosis checkpoint, signal regulatory protein α (SIRPα). 457 SIRPα is expressed by APCs and binds to the "don't eat me signal", CD47 expressed by cancer cells as an immune evasion mechanism to prevent phagocytosis. The group coloaded cGAMP and siRNA into particles, which had a diameter of ∼100 nm and were comprised of PEG-block-PLGA copolymers and the cationic lipid DOTAP.…”
Section: Delivery Technologies For Sting Pathway Agonists 61 Nanotech...mentioning
confidence: 99%
“…Using ovalbumin (OVA)-expressing melanoma as a model, it has been demonstrated that NP siSIRPa/cGAMP stimulated the activation of OVA-specific CD8 + T cells and induced holistic anti-tumor immune responses by reversing the immunosuppressive phenotype of APCs. 132 Nanoparticles loaded with STING agonists are also used combination with an immune checkpoint inhibitor or other therapy strategies for cancer treatment. 133 It has been found that lipid nanoparticles containing the STING agonist (STING-LNPs) efficiently induced activation of NK cells and are beneficial for cancer immunotherapy.…”
Section: Nanoparticles Targeting Dna Sensing Cgas/sting Pathwaysmentioning
confidence: 99%
“…The potent adjuvant effect was associated with lymphoid and myeloid cell population alterations in the tumor and tumor-draining lymph node. Lu et al (2021) developed a co-delivery immunotherapeutic strategy of the phagocytosis checkpoint (signal regulatory protein α, SIRPα) silencer and stimulator of interferon genes (STING) of APCs. A small interfering RNA targeting SIRPα (siSIRPα) and a STING agonist (cGAMP) were encapsulation into PLGA-based polymeric nanoparticles using the double emulsification method.…”
Section: Tumor Microenvironment Modulationmentioning
confidence: 99%